Analisis Pengembangan Usaha Produksi Ikan Pada Nelayan Kecamatan Pulau Ende di Kabupaten Ende - Lambertus Langga (ANALISIS, 2020)
One of the results is from the agriculture subsector in Pulau Ende District, Ende Regency. ishery products are the main livelihood to support his family. This study aims to determine how the influence of capital, labor, and sea time on fish production and to find out how much influence the capital, labor, sea time, on fish production. Population in the study were 5345 people and 98 people were sampled. This research uses interview methods and analyzed with quantitative descriptive analysis method which is done by describing all data in percentage numbers and frequency tables. The results showed that there was an effect of capital, labor, and sea fishing variables on fish production in Pulau Ende District. The test results obtained from the capital score indicator obtained at 3.24 which can be interpreted that the amount of capital that must be spent on fishing operations is expensive. Labor Indicator score obtained by 2.7 which means that the workforce needed is relatively much in fishing activities. For the old indicator of fishing the score obtained is 2.1 which can be interpreted as the time required for fishing activities takes a long time. Suggestions that can be taken by the Ende Regency Government should be more counseling and assistance in the form of nets, engines and motor boats. Fishermen don't wait for help, don't over-exploit fishing that is still too close to the beach and longer at sea.